National trends in the United States of America physician assistant workforce from 1980 to 2007 - Salling Mark; Cyran Ellen; He Xiaoxing Z (BMC, 2009)
Abstract Background The physician assistant (PA) profession is a nationally recognized medical profession in the United States of America (USA). However, relatively little is known regarding national trends of the PA workforce. Methods We examined the 1980-2007 USA Census data to determine the demographic distribution of the PA workforce and PA-to-population relationships. Maps were developed to provide graphical display of the data. All analyses were adjusted for the complex census design and analytical weights provided by the Census Bureau. Results In 1980 there were about 29 120 PAs, 64% of which were males. By contrast, in 2007 there were approximately 97 721 PAs with more than 66% of females. In 1980, Nevada had the highest estimated rate of 40 PAs per 100 000 persons, and North Dakota had the lowest rate (three). The corresponding rates in 2007 were about 85 in New Hampshire and ten in Mississippi. The levels of PA education have increased from less than 21% of PAs with four or more years of college in 1980, to more than 65% in 2007. While less than 17% of PAs were of minority groups in 1980, this figure rose to 23% in 2007. Although nearly 70% of PAs were younger than 35 years old in 1980, this percentage fell to 38% in 2007. Conclusion The trends of sustained increase and geographic variation in the PA workforce were identified. Educational level, percentage of minority, and age of the PA workforce have increased over time. Major causes of the changes in the PA workforce include educational factors and federal legislation or state regulation.